Pharmacologic androgen deprivation and cardiovascular disease risk factors: a systematic review. (May 2015) - Romo, Matthew L.; McCrillis, Aileen M.; Brite, Jennifer; Reales, Dalicia; Dowd, Jennifer B.; Schooling, C. Mary
Abstract Background Pharmacologic androgen deprivation therapy (ADT) is widely used to treat prostate cancer. Observational studies suggest ADT is associated with cardiovascular disease and its risk factors; however, such studies may be subject to bias. Our objective was to evaluate the effect of ADT on cardiovascular disease risk factors using data from randomized controlled trials (RCTs). Materials and methods We conducted a systematic review using MEDLINE and MEDLINE In‐Process (1950–June 2013), EMBASE (1974–June 2013) and Web of Science (1900–June 2013) for all RCTs in men with prostate cancer that compared pharmacologic ADT (i.e. use of gonadotropin‐releasing hormone agonist or antagonist) with a group that did not receive ADT and reported data on cardiovascular disease risk factors including blood pressure, cholesterol, triglycerides, fibrinogen, biomarkers of insulin sensitivity, adiposity and C‐reactive protein. We also searched for ongoing or unpublished trials. This study was registered at the PROSPERO International Prospective Register of Systematic Reviews (CRD42013005035). Results Of the 3272 unique publications identified in our systematic review, we did not identify a single RCT that reported data on any cardiovascular disease risk factor. We were unable to locate unreported data from corresponding authors or study sponsors. Conclusions There is a lack of published, reliable evidence describing the effects of ADT on cardiovascular disease risk factors. RCTs have likely collected data on these risk factors as part of routine study monitoring; however, these data have not been published. To understand the effect of ADT on cardiovascular morbidity, these data must be made available to the scientific community.